Depression and resting state heart rate variability in children and adolescents: a systematic review and meta-analysis - Koenig, Julian; Kemp, Andrew H.; Beauchaine, Theodore P.; Thayer, Julian F.; Kaess, Michael (Clinical psychology review, 2016)
Among adults, depression is associated with reduced vagal activity, as indexed by high frequency heart rate variability [HF-HRV]), which correlates inversely with depression severity. Available evidence in depressed children and adolescents remains to be reviewed systematically. A search of the literature was performed to identify studies reporting (i) HF-HRV in clinically depressed children/adolescents relative to controls (k=4, n=259) and (ii) the association between HF-HRV and depressive symptoms as measured by standardized psychometric instruments in children and adolescents (k=6, n=2625). Random-effects meta-analysis on group differences revealed significant effects that were associated with a moderate effect size (Hedges' g=−0.59; 95% CI [−1.05; −0.13]), indicating lower resting state HF-HRV among clinically depressed children/adolescents (n=99) compared to healthy controls (n=160), consistent with findings among adults. While no correlation between HF-HRV and depressive symptom severity was observed (r=−.041 [−0.143; 0.062]), these additional correlational findings are limited to non-clinical samples. Findings have important clinical implications including a potentially increased risk for future physical ill health and also the identification of potential new treatment targets in child and adolescent depression.
Gesehen am 29.04.2020